HEMODYNAMIC ANALYSIS OF THE BLOOD FLOW IN CAROTID ARTERY WITH PATHOLOGICAL GEOMETRY - E. D. Vitkouski; I. Y. Bazik; D. A. Baliuk; N. S. Davydova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The modeling of blood flow of internal carotid artery with different types of aneurysms is presented. Based on the data obtained from the CT scan and magnetic resonance imaging the 3D models of divisions with different types of aneurysms in carotid artery were made. According to the 3D models' data the flow simulation with the ANSYS sofware pack was made. That is how the records of blood velocity at diferent divisions and shearing stress at the vascular walls have been received. This particular method can be used for examination of progression and enlargement of vascular aneurysms of human body.